Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2019
DOI: 10.1145/3292500.3330758
|View full text |Cite
|
Sign up to set email alerts
|

Actions Speak Louder than Goals

Abstract: Assessing the impact of the individual actions performed by soccer players during games is a crucial aspect of the player recruitment process. Unfortunately, most traditional metrics fall short in addressing this task as they either focus on rare actions like shots and goals alone or fail to account for the context in which the actions occurred. This paper introduces (1) a new language for describing individual player actions on the pitch and (2) a framework for valuing any type of player action based on its i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 15 publications
0
50
0
5
Order By: Relevance
“…In Fig. 4 (right), three teams (final ranking) are considered: Manchester City (1), Chelsea (5), and Newcastle United (10). As Fig.…”
Section: Hpus Verification and Application To Premier Leaguementioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 4 (right), three teams (final ranking) are considered: Manchester City (1), Chelsea (5), and Newcastle United (10). As Fig.…”
Section: Hpus Verification and Application To Premier Leaguementioning
confidence: 99%
“…Football 5 has simultaneously been an influential sport and important industry around the globe [15]. Estimate has shown that the FIFA World Cup Qatar 2022 entertained over 5 billion viewers 6 , and it has also been established to be a pillar industry for countries like Italy and Great Britain [35].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the data also contains extraneous information such as changes in weather that are not crucial for analysis. The SPADL representation [6] addresses these concerns by converting event streams to a uniform representation designed to facilitate analysis. 2 Hence, we first transform our data into this format.…”
Section: Describing Actionsmentioning
confidence: 99%
“…Therefore, it is only recently that a data-driven approach has started to gain attention. Nevertheless, numerous approaches, from the simple aggregation of individual/team play statistics (Novatchkov and Baca, 2013), to complex methods, such as those that use gradient boosting to model the value of actions (Decroos et al, 2018a). In general one can observe two different types of analysis.…”
Section: Football Analyticsmentioning
confidence: 99%
“…In this case, an action is usually valued then aggregated by either player or team. (Decroos et al, 2018a) assigned values to on-ball action actions by measuring their effect on the probabilities that a team will score. In turn, (Fernandez and Bornn, 2018) proposed a method to value off the ball actions by estimating pitch value with a neural network.…”
Section: Football Analyticsmentioning
confidence: 99%